Von Hippel-Lindau disease in a pregnant lady - Choudhury, T; Jahan, S; Kamal, M; Hossain, MM; Khan, ZR (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):184-187 The abstract of this article is available on the PubMed website